A fiziko-teologizmus irodalmának hazai forrásai - Imre, Mihály (Studia Litteraria, 2020)
Our aim is to reimagine the Hungarian reception of physico-theology, demonstrating its significance in terms of the history of science and cultural science, and to present, with attention to other European sources and parallels, the cultural and literary process that leads us to the beginnings of the oeuvre of Mihály Fazekas and to the works of his contemporaries. We seek to obtain a deeper knowledge of the Hungarian and international sources of physicotheology in terms of the science of history in a Protestant environment in the 18th century, as well as of the first appearance of physico-theology in school education, scientific training and schools. In this endeavour, without attempting to be exhaustive, we have extended the sources to works of piety literature and liturgical literature. The scientific collections, manuscripts and printed materials of the Reformed College of Debrecen and the Reformed College of Sárospatak have been the subjects of this research, although western European sources have been used in the research as well. The principles of physico-theology were first widely introduced in Hungarian language in the works of Benjámin Szőnyi, followed by many of his contemporaries later on in the second half of the 18th century.